Attenuated Lower Limb Stretch-Shorten-Cycle Capacity in ACL Injured vs. Non-Injured Female Alpine Ski Racers: Not Just a Matter of Between-Limb Asymmetry - Matthew J. Jordan; Matthew J. Jordan; Matthew J. Jordan; Nathaniel Morris; Sophia Nimphius; Per Aagaard; Walter Herzog (Frontiers Media S.A., 2022)
A retrospective analysis of routine countermovement jump (CMJ) testing, a coupled eccentric-concentric (stretch-shorten-cycle: SSC) movement, was performed in female elite alpine skiers with anterior cruciate ligament (ACL) reconstruction (ACLR) and without ACLR. A total of 567 tests obtained from the daily training environment were analyzed in 41 elite female athletes (non-injured control: n = 30, ACLR: n = 17), including n = 6 athletes with pre-injury data, between 16 and 32 years of age from alpine ski racing (n = 32) and skier cross (n = 9). Bilateral CMJ testing was conducted on a dual force plate system, and the limb-specific vertical ground reaction force (Fz) was analyzed to obtain the net eccentric deceleration impulse (Ecc), lower limb stiffness (Stiff), maximal vertical jump height (JH), peak external mechanical power (PP) exerted on the body center of mass (BCM), modified-reactive-strength-index (RSImod), and the loss in BCM velocity during the final phase of the takeoff Δ(Vmax-Vtakeoff). Eccentric and concentric phase-specific between-limb asymmetry indexes (AIs) were also calculated. Additive mixed effects models (AMMs) were used to compare the age-dependent and post-injury time course change between groups. The mean values for non-injured controls >25 years of age were used as a comparative benchmark for recovery given the absence of pre-injury data. Net eccentric deceleration impulse increased and Δ(Vmax-Vtakeoff) decreased with age for the non-injured control group (p < 0.001) while between-limb AI (mean ± SD) fell between 1 ± 5% for the concentric phase and 3 ± 7% for the eccentric deceleration phase. Between-limb asymmetry became smaller in ACLR skiers with time-from-surgery to reach non-injured control values by 2 years, but SSC function, such as JH and PP, remained depressed up to 5 years post-surgery (p < 0.01), indicating impairments in SSC function. This highlights the importance of evaluating SSC performance capacity alongside vertical jump force-time asymmetries in female ACLR alpine skiers.